A Playful Proposal on Summaê at IFG – Campus Luziânia - Lima, Igor dos Santos; Pereira dos Santos, Wagner (Brazilian Journal of Science, 2022)
This paper presents an analysis and adaptation of the teaching methodology called Summaê, in order to mitigate the difficulties in mathematics of first year students of the IFG - Câmpus Luziânia, of the Integrated Technical Courses of Building, Information Technology and Chemistry. Summaê was idealized by Professor Ricardo Fragelli and is an active methodology based on a ludic game of questions and answers, where the students create the questions through videos that are previously recorded. The application proposal is for the content of exponential and logarithmic functions and can be adapted for other contents and educational institutions. The analysis of the proposal will be carried out in the perspectives of the authors Grando, Kishimoto and Muniz. The Summaê adapted and important as an active methodological practice, because second Grando, Kishimoto and Muniz or apprenticed by the student is potentiated from his engagement during the game and the teacher in this context, he has a fundamental role of mediator and intervener. The theme chosen for this article was motivated by two indices. Given these indices, the motivation for the elaboration of the proposal adapted to Summaê in the discipline of Mathematics arises so that the teacher can, apart from the expository classrooms, add or play to mitigate these retention indices as well as motivate and engage the students. This proposal also aims to motivate teachers from other disciplines, pois or Summaê as a methodology can also be applied to other contents, making only the necessary adaptations according to the reality of the teacher in his discipline.